Pengembangan Bahan Ajar Pendidikan Pancasila berbasis Profil Pelajar Pancasila dimensi Bernalar Kritis dan Kreatif - Fajriyah, Khusnul; Wijayanti, Arfilia; Kiswoyo, Kiswoyo; Nugroho, Bagus Ardi (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2024)
The implementation of the independent curriculum at the school level faces obstacles related to the availability of teaching materials that accommodate the development of school student profiles, especially the dimensions of critical and creative reasoning. On the other hand, critical reasoning skills are important for students in the era of rapid information and communication technology. The purpose of this study is to develop teaching materials containing the Pancasila Student Profile with critical and creative reasoning dimensions that are feasible/valid and have good acceptance. The design of this study uses Research and Development with the Borg and Gall model. Distribution of questionnaires, interviews, and observations were carried out to obtain research data. The results of the study indicate that the Pancasila education teaching materials based on the Pancasila student profile with critical and creative reasoning dimensions have been declared valid and suitable for use. This is based on the results of the assessment of teaching materials by three experts with an average value of 89.6% with a very good category. The results of the teacher response questionnaire also showed that this teaching material was acceptable.